Uso de Herramientas digitales de trabajo colaborativo por los docentes de la Unidad Educativa Fiscomisional Mercedes de Jesús Molina, año lectivo 2022-2023. - Salazar Giron, Carla Silvana (2024)
Digital tools for collaborative work have transformed how you work and learn; they are indispensable because they seek to facilitate remote collaboration so that the devices of a company perform their tasks with ease, therefore, in the educational field they are an optimal option for teachers to implement these tools with their students, regardless of whether they are in the same physical place or not, for this reason, this research seeks to diagnose the collaborative work digital tools use by teachers of the Unidad Educativa Fiscomisional Mercedes de Jesús Molina, school year 2022-2023. The methodology starts in the function of the deductive method, quantitative approach, descriptive scope and with a cross-sectional research design; twelve tools used by teachers were identified, which were distributed by dimensions, such as communication, knowledge management, file storage and project creation, from this the research instrument was built for data collection based on different authors, applied through the survey technique, whose measurement indicator corresponds to the Likert frequency scale and dichotomous questions of YES and NO, which diagnosed the collaborative work digital tools most used by the teachers of the institution, where in the YES answer alternative, the Zoom platform stood out in the communication dimension, Google Drive for file storage, Genially for the creation of projects and Blogger for knowledge management; on the other hand, in the NO alternative answer, of the communication dimension was Join.me, Reddit for knowledge management, Padlet and Mindmeister for project creation, and Dropbox for file storage. Keywords: Digital Tools, Collaborative Work, educational technology, Educational System